Character Education : Implementation and Issues at SDN Pandanwangi 02 - Sitaba, Fitra Aulia Rizkinanda; Utama, Candra (Universitas Negeri Malang, 2024)
This research explores the implementation of character education and its associated challenges among students at SDN Pandanwangi 02. The purpose of this research is to explore teachers' efforts in understanding the implementation of character education and addressing various issues in character education such as students' reading delays at the school. This study employs a qualitative research methodology, utilizing observation and interviews as data collection techniques. The results indicate that teachers address issues in character education by providing additional learning for students experiencing reading delays and integrating character education through routine activities such as group prayers and religious studies. However, the implementation of character education faces additional challenges, such as a lack of student discipline in some areas. These findings highlight the importance of character education in elementary schools as the foundation for shaping students' good character. Therefore, further efforts are needed to enhance the effectiveness of character education at SDN Pandanwangi 02 in molding students with desired character values.